Effects of spray-dried animal plasma source on weanling pig performance - M U Steidinger; P R O'Quinn; J C Woodworth; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
Three studies were conducted to evaluate the effects of different spray-dried animal plasma (SDAP) sources on weanling pig performance. For this study, different sources of SDAP were obtained from each of the four largest marketers. In each experiment, a different lot of each of the four plasma sources was used. Pigs were fed either a control diet or one of four diets containing different plasma sources added at 5.0 % of the total diet. The results of these experiments suggest that larger differences occur between lots or batches of SDAP then between sources of SDAP, when weanling pig performance is used as the response criterion. More research must be done to determine the factors responsible for the differences between batches of SDAP.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Starter pigs; Spray-dried animal plasma; Performance